Caracterização da vulnerabilidade à erosão costeira com o uso de geotecnologias e geoindicadores nas praias do município de Lucena (PB), Brasil - Pereira, José Charriere Gomes (2025)
Coastal erosion is a dynamic phenomenon that directly affects the stability of coastal zones and can be intensified by natural and anthropogenic factors. This study aimed to characterize the vulnerability to coastal erosion in the beaches of Lucena (PB), Brazil, using geotechnologies and geoindicators. To achieve this, methodologies for analyzing shoreline variation were applied through the CASSIE (Coastal Analysis System via Satellite Imagery Engine) tool, combined with the identification of specific geoindicators such as beach morphology, dune presence, wave exposure, coastal vegetation, and soil impermeability. Field data were collected and integrated with remote sensing images to obtain a coastal vulnerability index. The results indicate significant shoreline variations over the past decades, highlighting sectors with trends toward intense erosion and areas with relative sedimentary stability. The integration of geotechnologies with geoindicators enabled the identification of spatial patterns of vulnerability, providing support for coastal planning and environmental management in the municipality. It is concluded that the adopted methodology proved to be efficient in assessing coastal vulnerability, serving as an essential tool for decision-making in public policies aimed at mitigating the impacts of erosion and preserving coastal ecosystems.